An experimental and modeling study of autoignition characteristics of two real low-octane gasoline fuels in a heated rapid compression machine at elevated pressures. (1st July 2021) - Li, Jing; Zhu, Jizhen; Wang, Sixu; Feng, Yuan; Zhou, Wei; Qian, Yong; Yu, Liang; Lu, Xingcai
Highlights: The ignition delays of two real low-octane gasolines were measured in an RCM. Two six-component gasoline surrogates were formulated for GCI engines. Cycloalkane chemistry is more important than isooctane in the autoignition behavior. EGR effects on ignition were also investigated under engine-like conditions. Abstract: Gasoline compression ignition (GCI) has received much attention due to its high efficiency and low emissions. The low-octane gasoline can be applied to extend the GCI operating range. However, there is limited knowledge of the autoignition chemistry for the low-octane gasoline. In this study, the ignition delay times (IDTs) of two real distillate gasoline fuels with research octane numbers (RON) of 72 and 83, denoted as G72 and G83 respectively, were measured in a heated rapid compression machine (RCM) over wide ranges of pressures (10, 15 and 20 bar), temperatures (670–940 K), equivalence ratios (0.5, 1.0 and 2.0), and diluted conditions. Both G72 and G83 exhibit apparent two-stage ignition characteristics with negative temperature coefficient (NTC) behavior in the low-to-intermediate temperature region. Considering the effects of exhaust gas recirculation (EGR) technology on GCI combustion, ignition characteristics of low-octane gasolines under simulated-EGR conditions were also studied by varying the N2 /O2 ratio while fixing the fuel mole fraction. It is found that the NTC region moves towards the higher temperature side as the oxygen concentration decreases. Moreover, two six-component surrogates were formulated for G72 (28.4% n -pentane, 3.5% n -heptane, 24.5% 2-methylhexane, 26.3% 2, 2, 4-trimethylpentane, 13.8% cyclopentane, and 3.3% toluene, by mol.), and G83 (16.5% n -pentane, 10.6% n -heptane, 5.6% 2-methylhexane, 37.4% 2, 2, 4-trimethylpentane, 10.2% cyclopentane and 19.7% toluene, by mol.). Kinetic modeling was then conducted using a published kinetic model coupled with proposed surrogates. Sensitivity analysis results further revealed that compared with isooctane, cycloalkane chemistry is more important in the overall autoignition behavior at low temperatures.